Rola ogniw pośrednich w strukturze zarządzania przemysłem w XXX-leciu PRL - Majchrzak, Jadwiga (Wydział Prawa i Administracji UAM, 1976)
The article presents changes in functions of intermediary cells in the structure of management of an industry against a background of industrial development and reforms in management system. The general direction of these .changes, according to formal assumptions and to reality, has been based on transformation of intermediary cells from omits, transmitting tasks and information, into independent economic subjects. The real scope (of changes, however, hals not fulfilled the formal assumptions; It has been (narrower. The degree of decisive independence of intermediary cells has been limited, and in (management of enterprises (injunctions have dominated. The reasons of such state of thinigs are very complex. They can be, however, attributed to insufficient independence of intermediary cells, to the lack of comprehensive reforms and to the diversity of forms of grouping (enterprises).
The Role of Intermediary Cells in the Structure of Management of an Industry in the Thirty Years of the Polish People's Republic